Pendekatan Model Fungsi Non-Linier Perubahan Suhu Pada Pencampuran Zat Cair Menggunakan Bantuan Hukum Entropi Goen - Stephanus Ivan Goenawan (Cylinder : Jurnal Ilmiah Teknik Mesin, 2026)
The Second Law of Thermodynamics, also known as the Law of Entropy, explains that the level of disorder or entropy will continue to increase in a closed system operating in forward time. Along with its development, a further concept emerged called the Second Law of Thermodynamics Point One (2.1) or Goen's Law of Entropy. This law states that the average entropy in a process in the forward direction is always smaller than the average entropy in the backward direction. The backward average entropy process is the opposite of the forward average entropy, which works on the heat function to reflect the forward process. Applying Goen's Law of Entropy, a non-linear model based on the function of time can be created that describes the change in temperature of the combination of two liquids, starting from the initial conditions before mixing to reaching thermal equilibrium in a closed container. The results of this non-linear exponential modeling in mixing two liquids prove the importance of Goen's Law of Entropy as a development of the Second Law of Thermodynamics, with significant benefits in explaining the phenomenon of heat transfer and the process towards equilibrium.